International consensus guidelines for phosphoglucomutase 1 deficiency (PGM1‐CDG): Diagnosis, follow‐up, and management. Issue 1 (15th September 2020) - Altassan, Ruqaiah; Radenkovic, Silvia; Edmondson, Andrew C.; Barone, Rita; Brasil, Sandra; Cechova, Anna; Coman, David; Donoghue, Sarah; Falkenstein, Kristina; Ferreira, Vanessa; Ferreira, Carlos; Fiumara, Agata; et al.
Abstract: Phosphoglucomutase 1 (PGM1) deficiency is a rare genetic disorder that affects glycogen metabolism, glycolysis, and protein glycosylation. Previously known as GSD XIV, it was recently reclassified as a congenital disorder of glycosylation, PGM1‐CDG. PGM1‐CDG usually manifests as a multisystem disease. Most patients present as infants with cleft palate, liver function abnormalities and hypoglycemia, but some patients present in adulthood with isolated muscle involvement. Some patients develop life‐threatening cardiomyopathy. Unlike most other CDG, PGM1‐CDG has an effective treatment option, d ‐galactose, which has been shown to improve many of the patients' symptoms. Therefore, early diagnosis and initiation of treatment for PGM1‐CDG patients are crucial decisions. In this article, our group of international experts suggests diagnostic, follow‐up, and management guidelines for PGM1‐CDG. These guidelines are based on the best available evidence‐based data and experts' opinions aiming to provide a practical resource for health care providers to facilitate successful diagnosis and optimal management of PGM1‐CDG patients.